Practical industrial data communications : best practice techniques - Reynders, Deon.; Mackay, S.; Wright, E. (Newnes, 2005)
The objective of this book is to outline the best practice in designing, installing, commissioning and troubleshooting industrial data communications systems. In any given plant, factory or installation there are a myriad of different industrial communications standards used and the key to successful implementation is the degree to which the entire system integrates and works together. With so many different standards on the market today, the debate is not about what is the best - be it Foundation Fieldbus, Profibus, Devicenet or Industrial Ethernet but rather about selecting the most appropriate technologies and standards for a given application and then ensuring that best practice is followed in designing, installing and commissioning the data communications links to ensure they run fault-free. The industrial data communications systems in your plant underpin your entire operation. It is critical that you apply best practice in designing, installing and fixing any problems that may occur. This book distills all the tips and tricks with the benefit of many years of experience and gives the best proven practices to follow. The main steps in using today's communications technologies involve selecting the correct technology and standards for your plant based on your requirements; doing the design of the overall system; installing the cabling and then commissioning the system. Fiber Optic cabling is generally accepted as the best approach for physical communications but there are obviously areas where you will be forced to use copper wiring and, indeed, wireless communications. This book outlines the critical rules followed in installing the data communications physical transport media and then ensuring that the installation will be trouble-free for years to come. The important point to make is that with todays wide range of protocols available, you only need to know how to select, install and maintain them in the most cost-effective manner for your plant or factory - knowledge of the minute details of the protocols is not necessary. *An engineer's guide to communications systems using fiber optic cabling, copper cabling and wireless technology *Covers: selection of technology and standards - system design - installation of equipment and cabling - commissioning and maintenance *Crammed with practical techniques and know how - written by engineers for engineers.
Introduction - general topics such as the OSI model, systems engineering concepts, physical (layer 1) connections, protocols, and noise and ingress protection, Media, specifically conductive media viz. copper (coax, UTP, STP) and fiber, hysical layer standards - EIA-232, EIA-485, 4-20 mA and IEC 61158, Well-known industrial protocols such as TCP/IP, Modbus, DNP3 and IEC 60870, Popular industrial networks (both old and new) such as Industrial Ethernet, AS-i, DeviceNet, Profibus, Foundation Fieldbus, Modbus Plus, Data Highway Plus and HART, Wireless technologies, including VSAT, IEEE 802.11 and wireless point-to-point, Selection methodology - the appropriate steps to be taken in choosing the components for an industrial data communications system, Recommended practice in installing, commissioning and troubleshooting industrial data communications systems.
Electronic resource.
Keywords: Data transmission systems; Industrial management -- Computer network resources; Computernetwerken; LAN; Draadloze communicatie; Electronic books